BP Deepwater Horizon: the value of sustainability accounting - Unerman, Jeffrey (Henry Stewart Talks, 2018)
This case study looks at the economic, societal, and environmental impact of the oil spill disaster, the BP Deepwater Horizon, in 2010. The speaker argues that if BP had factored in the possible environmental risks in its operational safety decisions, it could have saved many billions of dollars in reputational damage and fines.